2020
DOI: 10.1038/s41598-020-63766-2
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Functions of Astrocytes are Dependent Upon Tumor Necrosis Factor-Alpha

Abstract: Acute inflammation is a key feature of innate immunity that initiates clearance and repair in infected or damaged tissues. Alternatively, chronic inflammation is implicated in numerous disease processes. The contribution of neuroinflammation to the pathogenesis of neurological conditions, including infection, traumatic brain injury, and neurodegenerative diseases, has become increasingly evident. Potential drivers of such neuroinflammation include toll-like receptors (TLRs). TLRs confer a wide array of functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 64 publications
3
28
1
Order By: Relevance
“…Alternatively, it has been proposed that the cytokines originate from the contaminating microglia, whose cytokine secretion might be increased in the presence of astrocytes (Saura, 2007; Sola et al, 2002). However, recent investigations resolved this issue by using 99% pure astrocyte cultures and corroborated the finding that astrocytes release pro-inflammatory cytokines in response to stimulation of TLR (Li et al, 2020; Rodgers et al, 2020 ). Of note, even studies on microglia-depleted astrocyte cultures agree that astrocytes express functional TLRs, because they respond to TLR agonists by upregulating TLR expression ( Marinelli et al, 2015 ).…”
Section: Tlrs Modulate Astrocyte Function In Vitromentioning
confidence: 90%
See 1 more Smart Citation
“…Alternatively, it has been proposed that the cytokines originate from the contaminating microglia, whose cytokine secretion might be increased in the presence of astrocytes (Saura, 2007; Sola et al, 2002). However, recent investigations resolved this issue by using 99% pure astrocyte cultures and corroborated the finding that astrocytes release pro-inflammatory cytokines in response to stimulation of TLR (Li et al, 2020; Rodgers et al, 2020 ). Of note, even studies on microglia-depleted astrocyte cultures agree that astrocytes express functional TLRs, because they respond to TLR agonists by upregulating TLR expression ( Marinelli et al, 2015 ).…”
Section: Tlrs Modulate Astrocyte Function In Vitromentioning
confidence: 90%
“…This was attributed to the upregulation of matrix metalloproteinase 9 (MMP-9), which degrades the extracellular matrix proteins and interacts with cell surface protein CD44 to facilitate the mobility of astrocytes ( Dufour et al, 2010 , Hsieh et al, 2010 ). Exposure of astrocyte cultures to the TLR2 and TLR4 agonist LPS promotes astrocyte proliferation via the release of TNF-α ( Rodgers et al, 2020 ). In contrast, TLR3 has opposite effects on astrocyte proliferation.…”
Section: Tlrs Modulate Astrocyte Function In Vitromentioning
confidence: 99%
“…Similar to microglia, activated astrocytes themselves can produce and release TNF, giving rise to an autocrine/paracrine loop of activation and cytokine release [ 102 ]. However, it has been shown that astrocytes alone are not able to sustain an efficient inflammatory response, for which microglia-derived TNF and other factors are required [ 103 ].…”
Section: Impact Of Microglia-derived Tnf On Brain Functionsmentioning
confidence: 99%
“…Thus, it is likely that microglial cells, the first to be activated after injury, represent the main source of TNF in the CNS, which is released to trigger astroglial pro-inflammatory activation [ 72 , 97 ]. Reactive astrocytes, as final effector cells, gain the ability to self-maintain their pro-inflammatory state by further releasing TNF, leading to long-lasting detrimental effects [ 102 ]. To close the circle, reactive astrocytes are able to modulate microglial activity, through inhibition of microglial TNF expression and release [ 104 , 105 ].…”
Section: Impact Of Microglia-derived Tnf On Brain Functionsmentioning
confidence: 99%
“…Cytokines exert a transient immunomodulatory function at high local concentrations in autocrine or paracrine fashions [9][10][11]. They are also elevated in peripheral blood in endocrine fashion in some in ammatory diseases [12].…”
Section: Introductionmentioning
confidence: 99%